VOL-1 - "Patel, Vithalbhai V.; Saran, Gyanendra; Patel, Deepak V." (Gurgaon, 2014)
HardcoverThis book of the late Vithalbhai B. Patel has been acknowledged to be a vital contribution in the field of labour law due to its analytical approach and richness in content. The present edition contains essential Case law. The edition ensures that the reader is not unnecessarily burdened with a plethora of judgments in the field and will have an easy access to all shades of judicial opinion and is further assisted in locating the final word. The case law on each section and every significant sub-section has been arranged under headings and subheadings which are numbered and placed under a synopsis to facilitate the reader$1 (Bs search of law on the topic of his interest.s